2012
DOI: 10.1002/ajmg.a.35408
|View full text |Cite
|
Sign up to set email alerts
|

Sirenomelia and caudal malformations in two families

Abstract: We report on two families with co-occurrence of sirenomelia and caudal malformations. In the first family, the mother had undergone surgery for a short form of imperforate anus. Her first pregnancy was terminated because of bilateral renal agenesis with oligohydramnios. Her second pregnancy was interrupted because of sirenomelia. The second family was referred to us because of caudal malformation in their two children. The parents' spinal radiographs were normal. The first pregnancy resulted in a girl with imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Caudal dysgenesis is hypothesized to arise from a primary deficiency of caudal mesoderm (Duhamel, ; Alles and Sulik, ). This theory is supported by many authors (e.g., Duesterhoeft et al, ; Charlier et al, ; Thottungal et al, ; Gerard et al, ; Seidahmed et al, ; Moosa et al, ; Das et al, ; Lhuaire et al, ; Kaygusuz et al, ). Dias and Walker () suggested that a teratogenic event occurred during gastrulation that interfered with the formation of the notochord, resulting in abnormally developed caudal structures and concomitant neural tube defects.…”
Section: Sirenomelia and Its Overlap With Caudal Dysgenesismentioning
confidence: 69%
See 1 more Smart Citation
“…Caudal dysgenesis is hypothesized to arise from a primary deficiency of caudal mesoderm (Duhamel, ; Alles and Sulik, ). This theory is supported by many authors (e.g., Duesterhoeft et al, ; Charlier et al, ; Thottungal et al, ; Gerard et al, ; Seidahmed et al, ; Moosa et al, ; Das et al, ; Lhuaire et al, ; Kaygusuz et al, ). Dias and Walker () suggested that a teratogenic event occurred during gastrulation that interfered with the formation of the notochord, resulting in abnormally developed caudal structures and concomitant neural tube defects.…”
Section: Sirenomelia and Its Overlap With Caudal Dysgenesismentioning
confidence: 69%
“…Other reports concern monozygotic twins in which one of the twins was affected by sirenomelia and the other by imperforated anus (Akbiyik et al, ). Gerard et al () described a mother who had undergone surgery for an imperforate anus and whose first pregnancy was terminated because of bilateral renal agenesis in the fetus. Her second pregnancy was complicated by sirenomelia.…”
Section: Familial Recurrence and Occurrence Of Sirenomeliamentioning
confidence: 99%
“…This allows the conclusion that sirenomelia may exist as a pathologic entity distinct from CD. Interestingly, human cases with minimum or even absent dorsal skeletal and neurological component have also been reported [66], [67].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, human sirenomelia has mainly been considered sporadic since familial cases have only been reported very recently [27]. However, it should be noted that the lack of evidence for a major genetic influence in human mermaid syndrome may rely, at least in part, on the poor documentation of abortions [4], [28].…”
Section: Introductionmentioning
confidence: 99%
“…La publication récente de cas familiaux a stimulé la recherche de facteurs génétiques associés à la sirénomélie [8]. Des études expérimentales réalisées chez des rats induisant des mutations perte de fonction des séquences de signalisation du gène « Bone morphogenetic protein » (BMP-7) ou des mutations gain de fonction des séquences de signalisation du gène «retinoic acid » (RA) ont permis d'observer le développement d'un phénotype semblable à celui observé chez l'humain, associant la fusion des membres inférieurs à des malformations pelviennes sévères [9].…”
Section: Discussionunclassified